Pre-screening techniques for identification of samples suitable for radiocarbon dating of poorly preserved bones - Brock, F; Higham, T; Ramsey, C (Elsevier, 2010)
Under certain environmental conditions, post-depositional diagenetic loss of bone collagen can severely reduce the number of bones from a particular archaeological site that are suitable for stable isotopic analysis or radiocarbon dating. This study examined nearly 300 bones from 12 archaeological sites across southern England known to yield poor or variable preservation to try to identify one, or more, pre-screening technique(s) that would indicate suitable collagen preservation for radiocarbon dating. The most reliable method was shown to be the percent nitrogen (%N) of whole bone powder, which has an 84% chance of successfully predicting whether or not a bone will yield sufficient (i.e.>1% weight) collagen for dating.